Bubblegum inspired epoxidized natural rubber composites for superior mechanical and electrical properties. (4th October 2022) - Zhu, Jingyi; Liang, Yingpei; Si, Wanjie; Zhang, Shuidong
Abstract: For bubblegum, the tight interfacial adhesion between a sugarcoating and the inner gum base and the hardness of sugarcoating ensure its high performance. Inspired by bubblegum, epoxidized natural rubber/reduced graphene oxide/ferroferric oxide (ENR/rGO/Fe3O4: oENR) composites were prepared to simultaneously achieve robust mechanical and electrical properties. According to FTIR, Raman, XPS, SEM and TEM, the molecular chains on the surface of ENR particles interact with rGO to form N–C covalent and NH–O hydrogen bond interfacial interactions via a "hydrazine bridge", which was the same as the hard sugarcoating function in bubblegum. However, the molecular chains inside ENR particles were not crosslinked, and acted in a manner similar to that of the gum base in bubblegum. Remarkably, this bubblegum inspired structure offered efficient conducting pathways and enhancement for oENR. Consequently, the tensile strength of oENR with 4.71 wt% rGO content (oENR4.71 ) was 12.7 MPa, a 20.5-fold increment compared with that for neat ENR. Ductility was not impacted by the presence of filler. Strikingly, oENR possessed superior electrical conductivity of 0.1 S/cm and EMI SE of 40.6 dB with 99.97% absorbance efficiency. It displayed a 35.3 Gauge factor at low strain with sensitivity suitable for magnetic switching. Potential applications in electromagnetic interference shielding (EMI) and stretchable sensors were apparent. A novel approach for significantly improving both electrical and mechanical properties of epoxidized natural rubber has been demonstrated. This should facilitate potential application in multifunctional electronics. Graphical abstract: Image 1 Highlights: Segregated oENR with strong interfacial interactions were in-situ prepared. rGO act as crosslinking center to form interfacial linkage by hydrazine bridge. Tensile strength of oENR4.71 increase 20.5-folds without sacrificing ductility. oENR possess a percolation threshold of 0.15 wt% and conductivity of 50 S/m. oENR show applications in EMI shielding, stretchable sensor and magnetic switch.